Assessing ecological correlates of marine bird declines to inform marine conservation. Issue 1 (5th September 2014) - Vilchis, L. Ignacio; Johnson, Christine K.; Evenson, Joseph R.; Pearson, Scott F.; Barry, Karen L.; Davidson, Peter; Raphael, Martin G.; Gaydos, Joseph K.
Abstract Identifying drivers of ecosystem change in large marine ecosystems is central for their effective management and conservation. This is a sizable challenge, particularly in ecosystems transcending international borders, where monitoring and conservation of long‐range migratory species and their habitats are logistically and financially problematic. Here, using tools borrowed from epidemiology, we elucidated common drivers underlying species declines within a marine ecosystem, much in the way epidemiological analyses evaluate risk factors for negative health outcomes to better inform decisions. Thus, we identified ecological traits and dietary specializations associated with species declines in a community of marine predators that could be reflective of ecosystem change. To do so, we integrated count data from winter surveys collected in long‐term marine bird monitoring programs conducted throughout the Salish Sea—a transboundary large marine ecosystem in North America's Pacific Northwest. We found that decadal declines in winter counts were most prevalent among pursuit divers such as alcids (Alcidae) and grebes (Podicipedidae) that have specialized diets based on forage fish, and that wide‐ranging species without local breeding colonies were more prone to these declines. Although a combination of factors is most likely driving declines of diving forage fish specialists, we propose that changes in the availability of low‐trophic prey may be forcing wintering range shifts of diving birds in the Salish Sea. Such a synthesis of long‐term trends in a marine predator community not only provides unique insights into the types of species that are at risk of extirpation and why, but may also inform proactive conservation measures to counteract threats—information that is paramount for species‐specific and ecosystem‐wide conservation. Evaluación de las Correlaciones Ecológicas de las Declinaciones de Aves Marinas para Informar a la Conservación Marina